Cryptocurrency investment: Analysis by UTAUT with cultural moderators - Castro, Julyanne Lages de Carvalho (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Cryptocurrency assets, known for their high risk, have seen a significant increase in the number of users, driven by the search for new investment opportunities and portfolio diversification. This research aims to explore and evaluate the factors that determine the intention and behavior of investing in cryptocurrencies. Purpose: The main objective of the study is to understand the effects of the intention to invest in cryptocurrencies using a behavioral theory, adding cultural moderation to the investment behavior model. Method: Quantitative research that uses the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical lens, the research applied an online questionnaire and obtained 222 valid responses for analysis, data collected from February to May 2021. Data analysis was based on structural equation modelling, with estimation using the partial least squares method. Results: The results revealed the contribution that UTAUT has on the intention to invest in cryptocurrencies, and that the variables of performance expectancy, social influence and facilitating conditions affect the intention to invest in cryptos. Conclusions: The level of education, in the sample represented by the majority of risk-prone investors, was a significant and moderating factor in the variations in the result of using the UTAUT in the context of the behavior of cryptocurrency investors.